Instructional design of smart technology use in teacher digital educational environment - Sarzhanova, G.B.; Bobesh, R.S.; Smagulova, G.Zh.; Turkel, A.; Serikbayeva, N.B. (The Education and Science Journal. Scholarly journal, 2023)
Introduction. According to the provisions mentioned in Digital Kazakhstan Programme and Digital Teacher national project, the teacher today is regarded not just as an active user of the novel digital and smart technologies, but as the creator and transmitter of the authors’ digital educational content. The modern teacher is supposed both to adapt to and perform the professional activity within the digital setting of the educational institution and be able to design his/her own digital educational environment to transfer the educational content and organise effective “educator-learner” educational interaction. This situation brings us to the issue of the necessity for the teacher to be aware and master the potential possibilities provided by the smart technologies in realisation of the educational activity in terms of online and mixed learning; this, in its turn, conditions the search for the solutions for the effective instructional design of smart technology application in a teacher digital educational environment. Aim. The present study aims to substantiate the instructional design of the implementation model of smart technologies when designing teacher personal digital educational environment (on the example of the authors’ Smart Assistant software as a means of optimising teacher activities and organising an online and mixed educational process). Methodology and research methods. The following categories of research methods were used to reach the goal set: 1) theoretical: cybernetics method, generalisation, analogy, abstraction, visualisation, modelling, and classification; 2) empirical: surveys and interviews techniques, as well as mathematical and statistical data analysis approaches. During the experimental part of the study an online questionnaire survey on “Implementation of smart technologies in designing a teacher personal digital educational environment in the conditions of distance learning at a university” was conducted among 201 teachers of Karaganda Buketov University (Republic of Kazakhstan) and Dokuz Eylul University (Turkey) from 12 December 2022 to 30 April 2023. The aim of the experiment was to identify problems with the adaptation and implementation of smart technologies in designing a digital educational environment. For this purpose, the respondents answered fifteen questions and made suggestions for improving the university digital educational environment. Results and scientific novelty. The article substantiates the design of smart technology implementation in a teacher digital educational environment as a means of optimising his/her activity in organising online and mixed learning process (on the example of the authors’ software Smart Assistant), and identifies the problems with the adaptation and implementation of professional activities in the context of a digital educational environment. The characteristic features of the problems of teachers’ adaptation in a digital educational environment and the difficulties of smart technologies implementation in their professional activity are defined. Practical significance. The Smart Assistant software product was developed as a means of optimising the teacher’s activities in organising an online and mixed educational process.
Педагогический дизайн применения смарт-технологий в цифровой образовательной среде педагога
Diseño pedagógico para la aplicación de tecnologías inteligentes en el ámbito educativo digital del docente
Keywords: instructional design; digital educational environment of the university; digital competence of the teacher; smart technologies; teacher personal educational environment